The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.14710/jphtcr.v4i1.10245
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction is Dominant Factor Influencing of Nurse Performance in X Hospital Pekanbaru

Abstract: Introduction: The provision of optimal health services is determined by the quality of health workers. The research objective was to explore the factors that influence the performance of nurses in health service.Method: It was a quantitative analytic study with a cross-sectional design. A total of 58 nurses participated with a purposive random sampling technique. The data was collected by questionnaire and worksheets observation. The statistical analysis was done by Smart PLS (Partial Least Square).Result: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…This is consistent with the research conducted by Al-Otaibi (2020), which demonstrated a robust correlation between employee performance at Dawadami Hospital and job satisfaction. Similarly, (Ismainar et al, 2021) and (Asadollah Khadivi, 2019) discovered that job satisfaction was the most significant factor affecting the performance of hospital nurses. This finding is consistent with the research conducted by Baluyos et al (2019), which examined the level of satisfaction that teachers had with their own performance.…”
Section: The Influence Of Job Satisfaction On Icare Performance Of Mi...mentioning
confidence: 95%
“…This is consistent with the research conducted by Al-Otaibi (2020), which demonstrated a robust correlation between employee performance at Dawadami Hospital and job satisfaction. Similarly, (Ismainar et al, 2021) and (Asadollah Khadivi, 2019) discovered that job satisfaction was the most significant factor affecting the performance of hospital nurses. This finding is consistent with the research conducted by Baluyos et al (2019), which examined the level of satisfaction that teachers had with their own performance.…”
Section: The Influence Of Job Satisfaction On Icare Performance Of Mi...mentioning
confidence: 95%
“…Results indicate a high turnover rate among clinic staff members in Klinik as reported. Job satisfaction significantly impacts the productivity and efficiency of Human Resources in the Health Care Industry [86]. Employee engagement in the organization has a direct relationship with turnover.…”
Section: The Problem Statementmentioning
confidence: 99%